2012
DOI: 10.1017/s0022215112001442
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral congenital choanal atresia encountered in late adulthood

Abstract: To our knowledge, this is the oldest patient with bilateral congenital choanal atresia to be reported in the recent literature. This condition is rarely encountered in adulthood but should be considered as a possible differential diagnosis of persistent nasal obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 8 publications
0
25
0
3
Order By: Relevance
“…The comprising tissue may be bony or membranous 2 3. with a preponderance for mixed composition,3 however, it has also been suggested that with improving imaging technology it is becoming apparent that the vast majority, if not all, cases have some form of bony occlusion 5.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The comprising tissue may be bony or membranous 2 3. with a preponderance for mixed composition,3 however, it has also been suggested that with improving imaging technology it is becoming apparent that the vast majority, if not all, cases have some form of bony occlusion 5.…”
Section: Discussionmentioning
confidence: 99%
“…While there are cases in the literature of patients diagnosed with BCA in adulthood 1 2. these have predominantly been in developing nations where access to healthcare is less available and lower priority symptoms such as nasal discharge and mouth breathing may be less likely to receive the same extent of investigation as those in developed nations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In case of bilateral atresia, the ability at birth to breath spontaneously through the mouth depends on the species. Although primates, among them humans, are obligatory nasal breathers [2], there are a few reported cases who survived many years despite total nasal blockage due to bilateral CCA [5][6][7].…”
Section: Introductionmentioning
confidence: 99%